CAFF Report - Green Paper on AMAP-CAFF Coordinated Monitoring Effort - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (CAFF, 2008)
Arctic Council's CAFF Working Group Green Paper on AMAP-CAFF Coordinated Monitoring Effort.